Sistem Informasi Penjualan Online Hasil Tani Desa Blukbuk Berbasis Aplikasi Website. - Irfan Ricky Afandi; Yusuf Handika; Isa Faqihuddin Hanif; Dede Ismail (Prosiding Seminar Nasional Teknoka, 2020)
Blukbuk Village is a village where most of the people's livelihoods are in the agricultural sector. So far, the process of selling agricultural products in Blukbuk Village is still carried out conventionally. However, farmers in Blukbuk Village often experience difficulties in selling agricultural products to consumers. The purpose of this research is to assist farmers in Blukbuk Village in selling agricultural products to consumers through an online sales information system based on a website application using the PHP programming language and MySQL database. With the design of an online sales information system based on a website application, it is hoped that it can introduce agricultural products in Blukbuk Village to the wider community and can improve the economy in Blukbuk Village